Исследование систем радиолокации методом компьютерного моделирования - Малахов, С. И. (My University, 2018)
In these theses, we consider the acquisition of skills of correct and effective use of computer technology and methods of computer simulation in solving complex scientific and technical problems.
Keywords: радиолокация; компьютерное моделирование